Author's Response to Overlooked Skyhooks - Dennett, Daniel C. (Tufts Archival Research Center, 2005)
Dennett, Daniel C. "Author's Response to 'Overlooked Skyhooks.'" Metascience 7, no. 3 (November 1998): 500-501. [File also includes a copy of Campbell's review, pages 489-499.]